The role of governance and integrated reporting quality in stakeholder value creation/ Siti Mariam Mansor... [et al.] - Mansor, Siti Mariam; Hassan, Mohamat Sabri; Jaffar, Romlah; Abdullah, Maizatulakma (UiTM Press, 2024)
Stakeholders have the power to enhance or destroy firms’ value-creation capabilities, hence firms need to balance the interests of all stakeholders. Boards are argued to be the influential actors in this effort, but how boards contribute to stakeholder value creation (SVC) remains ambiguous. Hence, the present study aimed to fill this gap by examining the role of governance in SVC while examining whether the publication of quality integrated reports supports the boards’ role in SVC. The sample consisted of 714 firm-year observations of internationally listed firms that adopted integrated reporting (IR). The content analysis of the integrated reports was utilized covering 2018 to 2020. The results indicated a significant and positive impact of governance on SVC, supporting the notion of the team production theory. The analysis further revealed that IR quality only had a main effect on SVC but not a strengthening effect on the nexus between governance and SVC. These findings provide theoretical support for the boards’ function in advancing financial and non-financial value creation for the stakeholders. The important practical implication is the support that IR is more than mere corporate reports as it acts as a communication tool that facilitates stakeholder relationships, supporting the realization of SVC.